The Twofold Objectivity of Truth - Sankey, Howard (Filozofia Nauki, 2023)
Truth about matters of fact is objective. This is not just because truth is objective. It is also because facts are objective. An objective fact makes an assertion of that fact true. The objectivity of the fact adds a further element of objectivity to the objective truth of the assertion. True assertions of fact are true because truth is objective and because the facts that make them true are objective. True assertions of fact are objective twice over. Their objectivity is twofold. Or, at least, that is the point I seek to establish here.